HUBUNGAN KARAKTERISTIK SOSIAL EKONOMI PETANI DENGAN TINGKAT PENERAPAN MODEL PENGELOLAAN TANAMAN TERPADU PADI SAWAH DI DESA JOHO KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO - Choirotunnisa Choirotunnisa; Sutarto Sutarto; Supanggyo Supanggyo (Universitas Sebelas Maret, 2008)
This research aims to study the farmers ' social-economic characteristic and to study the application of integrated rice plant cultivation model as well as (o study the relationship between the farmers' social-economic characteristic and the application ofintegrated rice plant cultivation model in Joho Village, Sub District of Mojolaban, Sukoharjo Regency. Basic method employed in the study was descriptive analytical one. The research location was determined purposively. Meanwhile the sampling method used was simple random sampling and in order to find out whether or not there is the relationship between the farmers' socialeconomic characteristic and the application of integrated rice plant cultivation model, Rank Spearman (rs) correlation test was employed using program computer SPSS 12.0for windows. The result ofresearch indicates that most farmers after there are 50 years old (63,33%), land width to wide category (48,33%), informal education to medium category (68,33%), formal education to medium category (48,33%), income to low category (45%) and experience to medium category (66, 67%). Meanwhile in application of integrated rice plant cultivation model indicates that the application of superior variety component belongs to high category (48,33%), that of high quality seed component to medium category (60%), that ofyoung seed component to low category (50%), that ofplanting method to low category (51,6%), that of organic fertilizer component to low category (58,33), and that of location-specific fertilizer component to medium category (66, 67%). The Rank Spearman correlation test at confidence level of 95% shows that there is insignificant relationship between land domination width with the application ofintegrated rice plant cultivation model, while there is significant relationship between income and experience with the application of integrated rice plant cultivation model. Meanwhile at confidence level of99%, there is very significant relationship between the age, formal and informal education with the application of integrated rice plant cullivation model.